DNA-Compatible Suzuki-Miyaura Cross-Coupling Reaction of Aryl Iodides With (Hetero)Aryl Boronic Acids for DNA-Encoded Libraries - Siripuram, Vijay Kumar; Sunkari, Yashoda Krishna; Nguyen, Thu-Lan; Flajolet, Marc (Frontiers in Chemistry, 2022)
An efficient method for the C-C bond formation via water soluble Na2PdCl4/sSPhos mediated Suzuki-Miyaura cross-coupling reaction of DNA conjugated aryl iodide with (het)aryl boronic acids has been developed. This reaction proceeds at 37°C in water and acetonitrile (4:1) system. We also demonstrated that numerous aromatic and heteroaromatic boronic acids of different electronic natures, and harboring various functional groups, were highly compatible providing the desired coupling products in good to excellent yields. This DNA-compatible Suzuki-Miyaura cross-coupling reaction has strong potential to construct DNA Encoded Libraries (DEL) in the context of drug discovery.